Paul Kucharski, La Spéculation Platonicienne, Publications de la Sorbonne, Série "Etudes", tome I, Béatrice- Nauwerlaerts, París, 1971, 390 pp - Lértora Mendoza, Celina A. (1973)
Fil: Lértora Mendoza, Celina A. Fundación para el Estudio del Pensamiento; Argentina